Measurement of HbA2 by capillary electrophoresis for diagnosing β-thalassemia/HbE disease in patients with low hbf - Watcharee Prasing (2018)
Objective: Capillary electrophoresis (CE) has the ability to detect hemoglobin (Hb) A2 in the presence of HbE. The aim of this study was to compare levels of HbA2 measured by CE between β-thalassemia/HbE and homozygous HbE patients. Methods: Molecular analysis for diagnosing of β-thalassemia gene mutations and HbE was performed in 28 blood samples containing of HbE >75% and HbF levels varying from 5% to 15% quantified by highperformance liquid chromatography (HPLC). Levels of HbA2, HbE, and HbF were then measured using CE. Results: Nine patients were diagnosed with β-thalassemia/HbE disease and 19 with homozygous HbE. All patients with β-thalassemia/HbE disease and only one patient (5%) with homozygous HbE had HbA2 higher than 6.0%. Conclusions: The analysis of HbA2 level (>6.0%) by CE may be an alternative method for preliminary diagnosis of β-thalassemia/HbE with uncertain β-thalassemia/HbE disease and homozygous HbE.